Wear of coated carbide insert in machining of mild steel - Mohamad Saiful, Izwan Busu (2010)
This thesis deals with the wear of coated carbide insert in machining of mild steel. Machineability of mild steel is considered good although the cutting temperature is high. The characteristic of mild steel like high strength, high resistance to breakage and high modulus of elasticity has increased the tool wear of the coated carbide when it is used to machining the mild steel for long period. As a result, tool wear of the coated carbide inserts in machining of mild steel still need to be improved. The main objective of this project is to examine the progress of tool wear and determine the crater wear and flank wear of the tool in machining the mild steel in turning process. In this project, 33 full factorial design of experiments (DOE) was employed in STATISTICA software to plan and perform the experiment systematically so that any possible experimental error would be minimized. Machining variables considered are cutting length, cutting speed and feed rate. The variables for three levels were 90,120 and 150 m/min for cutting speed, 0.05, 0.1 and 0.15 mm/rev for feed rate and 60, 120 and 180 mm for cutting length respectively. Machining of mild steel was carried out by using the conventional lathe machine. After each experiment, flank and crater wear of the coated carbide inserts was investigated and measured by using optical microscope integrated with Image Analyzer. Experimental data was analyzed in STATISTICA. Flank and crater wear curves were then plotted using Minitab software. The result indicates that feed rate is the most significant parameter that influencing both the flank and crater wear compared to cutting speed and cutting length. Optical micrograph of tool wear shows the crater wear progressed faster than flank wear. Tool wear curves shows that when the number of experiments increases, the flank and crater wear increase monotonically.